Dispute Processes : ADR and the Primary Forms of Decision-Making - Roberts, Simon; Palmer, Michael (Cambridge : Cambridge University Press, 2005)
This wide-ranging study considers the primary forms of decision-making - negotiation, mediation, and umpiring - in the context of rapidly changing discourses and practices of civil justice across many jurisdictions. Much contemporary discussion in this field, and associated projects of institutional design, are taking place under the wide ranging but imprecise label of Alternative Dispute Resolution (ADR). If a common linking theme is sought, the authors argue that this must lie in a general shift of priorities as between judgement and settlement in ideological terms. This new edition brings together and analyses a wide range of materials dealing with dispute processes and the current debates on civil justice. With the help of a selection of texts beyond those ordinarily found in the emerging alternative dispute resolution literature it provides a broad, comparative perspective on modes of handling civil disputes, with the principal focus on the central processes of negotiation and mediation.
Title from publisher's bibliographic system (viewed on 02 May 2017).
Keywords: Dispute resolution (Law)